Strawberry Shelf Life, Composition, and Enzymes Activity in Response to Edible Chitosan Coatings. Issue 2 (3rd April 2017) - Badawy, Mohamed E. I.; Rabea, Entsar I.; A. M. El-Nouby, Mahmoud; Ismail, Rania I. A.; Taktak, Nehad E. M.
ABSTRACT: A series of active biodegradable coatings based on chitosan, gelatin, starch, and sorbitol with or without monoterpenes (geraniol and thymol) were prepared and applied on fresh strawberry fruit as postharvest treatments. The coated fruits were inoculated with fungal spores of Botrytis cinerea and stored for 7 days at 4 °C. Decay incidence, weight loss, anthocyanins, total soluble solids (TSS), total soluble phenolics (TSP), polygalacturonase (PGase), pectin-lyase (PLase), antioxidant activity, guaiacol peroxidase (G-POD), polyphenol oxidase (PPO), and catalase (CAT) were elucidated in the fruits of experimental sets and they were compared with that of controls. The coatings showed a significant effect on the development of quality variables, with the additional effect of geraniol and thymol as a function of the polysaccharide matrix. The coatings inhibited decay incidence, reduced weight loss, delayed changes in the contents of anthocyanin, TSS, and total soluble phenolics; inhibited the increase in G-POD and PPO activities; and retarded the reduction in CAT activity. Compared to the controls, all of the coatings had positive effects on the inhibition of cell wall degrading enzymes (PGase and PLase) and among all the tested coatings, T5, chitosan (1%) + starch (1%) + sorbitol (0.5%) + tween (0.05%) + thymol (0.02%) was the best. This formulation showed also the highest antimicrobial activity and the greatest effect on other physiochemical parameters and it can be suggested to use it as a useful coating agent for extending the shelf-life and maintaining quality of strawberry fruit.